اتفاق ابن تيمية مع النحاة ونقده لآرائهم / Ibn Taimiyyah’s Agreement with the Opinions of Nahwu Scholars and His Criticism of Their Opinions - Rizki Gumilar (Diwan : Jurnal Bahasa dan Sastra Arab, 2021)
تناول هذا البحث اتفاق ابن تيمية على آراء النحاة ونقده لآرائهم، فمن هذا البحث يستنتج الباحث أن ابن تيمية لم يكن متعصبًا لمذهب معين ذكرها في كتبه لتقوية آرائه النحوية، لأن منهجه النحوي مبني على الحجة والدليل وتجنب التقليد. ولذلك  نجده محايدا غير متعصب لرأي بعض دون آخر، بل تارة ذهب إلى مذهب البصريين، وتارة ذهب إلى ما ذهب إليه الكوفيون، وتارة أخرى انفرد برأيه المستقل مخالفًا لآرائهم.ونوع التحليل المستخدم في هذا المجال فهو التحليل الوصفي،وطريقة جمع البيانات هي الطريقة المكتبية.الكلمات المفتاحية  : ابن تيمية; آراء  النحاة; النقدAbstract:This study discusses Ibn Taimiyyah's agreement with the opinions of Nahwu scholars and his criticisms of their opinions, so from this research it will be concluded that Ibn Taimiyyah was never fanatical about certain schools of thought (mazhab) that are always used in his books to strengthen his opinion. This is because his principles in the science of nahwu are built on hujjah and dalil, as well as avoid taqlid. Therefore, we will find that he was never fanatical in only some opinions, but sometimes he followed the opinion of the Basrah scholars, on other occasions he followed the opinion of the Kufa scholars, sometimes he even chose his own opinion that contradicted theirs.The type of analysis used in this research is descriptive analysis, and the method of data collection is the library method.